Analisis Faktor-Faktor Yang Mempengaruhi Profitabilitas Pada PT. Bank Mega Tbk - Asri, Giovana Putri Damar; , Dra. Chuzaimah, MM (2016)
The purpose of this study was to analyze the effect of the Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Net Interest Margin (NIM) which influence to profitability. Bank Mega Tbk. In this test sampling techniques of time series, data types and sources of data used in this study by using secondary data obtained from the data end of each financial year at PT. Bank Mega Tbk. Data analysis methods used were normality test, autocorrelation, heteroscedasticity test, multicollinearity test, test descriptive statistics, regression analysis, t test, F test and Coefficient of determination(R2). By using the t test showed that the variables of the Loan to Deposit Ratio (LDR), Net-performing loans (NPL), Net Interest Margin (NIM) jointly significant effect on profitability (ROA). The results of the F test analysis found that the variable Loan to Deposit Ratio (LDR), Net-performing loans (NPL), Net Interest Margin (NIM) jointly significant effect on profitability. The results of the analysis of the coefficient of determination (R2) obtained Adjusted R square (R2) of 0.851, this shows that the profitability can be explained by the variable Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Net Interest Margin (NIM) was at 85 , 1%, while the remaining 14.9% is influenced by other factors beyond the variables studied. Keywords: Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Net Interest Margin (NIM)